(untitled) (Comparative & International Education Series, 2021)
The globalization efforts of U.S. institutions result in large-scale international branch campuses and overseas representative offices. This reflective case study explores a China Gateway Office (CGO) affiliated with a large, public, U.S. Midwestern research institution. The CGO has produced a robust global community by cultivating relationships between the home institution and the network abroad. The CGO establishes creative programs to extend the university’s outreach to students, faculty, alumni, partners, and researchers. The CGO leadership team navigated through the uncertainty of COVID-19 regarding travel bans, proposed political threat to research, and barriers for international student recruitment and study abroad. This case study adopts a reflective essaying approach to report on successful leadership strategies in times of crisis. This essay showcases how the CGO’s leadership team aptly responded to uncertainty under intense scrutiny and constraint in an ever-changing global environment.